OSTRACISM AND DEPRESSION AMONG OLDER ADULTS: A CASE OF PUNJAB, PAKISTAN - Hamid Bilal; Dr. Syeda Shahida Batool (International Journal of Contemporary Issues in Social Sciences, 2024)
Ostracism is the experience of being neglected or excluded from a social setting or interaction, and this negative social phenomenon is experienced by people of all ages. The present study was conducted to assess the relationship between ostracism and depression among older adults. A correlational study design along with purposive sampling was used to collect data from 200 older adults in Punjab, Pakistan. The age range of the participants was 60 to 98 years (M = 67.11, SD = 6.79). Demographic datasheet, Ostracism Scale for Older Adults and Geriatric Depression Scale were used to investigate the demographics of the participants and assess ostracism and depression respectively. Depression was found to have a significant positive correlation with ostracism and its dimensions (viz., social exclusion and social neglect). Furthermore, ostracism positively predicted depression. Older adults living in a joint family system scored significantly higher on social neglect. The present study highlighted the negative outcome of ostracism that is depression. Government can arrange awareness seminars regarding how ostracism can affect the older population and can introduce strategies and policies specifically tailored according to the needs of the older adults to combat the negative effects of ostracism.